First in the field : baseball hero Jackie Robinson - Dingle, Derek T. (New York : Hyperion Books for Children, 1998)
A biography which discusses the discrimination faced by Jackie Robinson, the baseball legend who became the first African-American to play Major League baseball for the Brooklyn Dodgers.
Includes bibliographical references (p. 48).
Wilson's Children.
Wilson's Junior High School.
Elem. School Library Collection.
7.3
3-6
Keywords: Robinson, Jackie, -- 1919-1972 -- Juvenile literature; Robinson, Jackie, -- 1919-1972.; Robinson, Jackie, -- 1919-1972.; Baseball players -- United States -- Biography -- Juvenile literature; African American baseball players -- Biography -- Juvenile literature; Discrimination in sports -- United States -- History -- 20th century -- Juvenile literature; Baseball players; African American baseball players; African Americans -- Biography; Baseball players -- Biography; African American baseball players -- Biography; Discrimination -- History; African Americans -- Biography; Baseball players -- United States -- Biography; Discrimination in sports -- History; African Americans -- Biography